Analysis of the Implementation Sipenda Application to Improving Transparency and Accountability of Local Tax Management in North Lombok Regency - Parasti, Azhilatul Annisa; Sukma, Paradisa (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research was conducted to find out how the implementation of the SIPENDA application improved the transparency and accountability of local tax management in North Lombok Regency. This research uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. Data in this study is from interviews with people who are direct users of the Sipenda application. the result of implementation of a management information system through the SIPENDA application at the Regional Revenue Agency of North Lombok District has succeeded in increasing transparency and accountability in local tax management through the implementation of a digital-based management system, which is characterized by an increase in the realization of local own-source revenue.